Gambaran Aspek Psikologis pada Pasien Hipertensi di Puskesmas Ranomuut Kota Manado - Lumintang, Yovita Faustina; Natalia M., Adriani; Mariana, Dina (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2023)
ABSTRACT Background Psychological Aspects are one of the causes of hypertension. Hypertension has been recognized as a major global public health problem. Hypertension is associated with an increased risk of death and the incidence of cardiovascular disease. The aim of the study was to determine the psychological picture of hypertensive patients at the Ranomuut Health Center. The method used is a type of quantitative research with a descriptive analysis design. The sample obtained amounted to 138 respondents. The research instrument is the Depression Anxiety Stress Scales (DASS) questionnaire. The data analysis methods use univariate analysis. According to the results obtained, the majority of patients have moderate Anxiety levels, as many as 104 respondents (75.4%), a normal Depression level, as many as 70 (50.7%), and a normal stress level, as many as 136 (98.6%). The conclusion is that there is an influence between the level of anxiety, stress, and depression and the blood pressure of people with hypertension. Advice for people with hypertension to be able to control psychological disorders of increased blood pressure in health institutions or health workers Keywords : Hypertension, Psychological ABSTRAK Latar Belakang Aspek Psikologis merupakan salah satu penyebab terjadinya penyakit hipertensi. Hipertensi telah diakui sebagai masalah kesehatan masyarakat global yang utama. Hipertensi dikaitkan dengan peningkatan risiko kematian dan kejadian penyakit kardiovaskuler. Tujuan penelitian adalah untuk mengetahui gambaran aspek psikologis pada pasien hipertensi di Puskesmas Ranomuut. Metode yang digunakan yaitu jenis penelitian kuantitatif dengan desain analisis deskriptif. Sampel yang diperoleh berjumlah 138 responden. Instrumen penelitian yaitu kuesioner Depression Anxiety Stress Scales (DASS). Metode analisis data menggunakan analisis univariat. Hasil diperoleh mayoritas pasien memiliki Tingkat Kecemasan sedang sebanyak 104 responden (75,4 %), Tingkat Depresi normal sebanyak 70 (50,7 %), Tingkat Stres normal sebanyak 136 (98,6 %). Kesimpulan bahwa ada pengaruh antara tingkat kecemasan, stres dan depresi dengan tekanan darah penderita hipertensi. Saran Bagi penderita hipertensi agar dapat mengontrol gangguan psikologis terhadap peningkatan tekanan darah di lembaga- lembaga kesehatan atau tenaga Kesehatan. Kata Kunci : Hipertensi, Psikologis